(untitled) (Eurasian Journal of Philology Science and Education, 2025)
Kozhanasyr is a satirical literary character widely known in Eastern culture, embodying folk wisdom and farsightedness. In the stories associated with his name, filled with humor and moral lessons, animalistic images occupy a special place, among which the image of the donkey stands out. This image serves to characterize such traits of human nature and personality as wisdom, submissiveness, patience, diligence, as well as foolishness and philistinism. In the narratives, the image of the donkey performs important cultural, symbolic, and social functions in revealing the essence of Kozhanasyr, his wisdom, and his life philosophy. The article focuses on the analysis of methods for identifying animalistic images and the peculiarities of their interpretation in the context of world literature and folklore. Particular attention is paid to the place of the donkey’s image in cultural and historical contexts, as well as its influence on social norms and stereotypes. At times, this figure acts as a secondary literary character involved in the storyline, while at other times it becomes a direct object of satire, turning into a tool for conveying philosophical and ethical ideas. In addition, the article examines the function of animalistic symbolism in reflecting social problems and negative traits of human behavior. Various methods and approaches to the identification of such images, their cultural impact, and their significance within the overall context of Kozhanasyr’s folklore texts are analyzed. The study concludes that the complex literary character revealed through animalistic imagery in Kozhanasyr’s stories represents a phenomenon that requires comprehensive scholarly investigation. Key words: Kozhanasyr, animalistic image, literary hero, humour, social idea, interpretation, identification.